Penerapan Workshop sebagai Upaya Meningkatkan Kompetensi Guru dalam Menulis Karya Ilmiah Di SDN 099/IX Danau Kedap - Ermawinda Ermawinda (Jurnal Gentala Pendidikan Dasar, 2020)
This study aims to obtain information and discuss about the application of the workshop as an effort to improve teacher competence in writing scientific papers at SDN 099 / IX Danau Kedap Odd Semester Academic Year 2019/2010. This type of research is a school action research consisting of two cycles with each cycle consisting of four stages, namely planning, implementation, observation and reflection. This research was conducted at SDN 099 / IX Danau Kedap in the odd semester of the 2019/2020 school year with research subjects teachers at SDN 099 / IX Danau Kedap totaling 8 teachers consisting of class teachers and subject teachers. Data collection techniques using observation, field notes, interviews and documentation. Data were analyzed using percentage and data reduction. The results showed that the workshop could improve teacher's pedagogical competence in writing scientific papers at SDN 099 / IX Danau Kedap by performing random presentations.